PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis quineensis Jacq) PADA MEDIUM ULTISOL YANG DIAPLIKASI KOMPOS Mucuna bracteata - Taufik Ristumoyo Rambe; Adiwirman; Wawan (UIR Press, 2019)
The first problem faced in cultivating oil palm is the procurement of seeds. Ultisol soil when used for breeding media has several problems such as having a wet saturation of less than 35% at a depth of 125 cm below the upper limit of the argillic horizon. Ultisol has an acidity level of less than 5.5, low to moderate organic matter and low nutrition. The addition of organic material such as the LCC Mucuna bracteata compost is highly recommended because it will improve the physical, biological, and chemical properties of the soil, so that it increases the availability of nutrients in the soil to be optimal. This study aims to determine the effect of LCC mucuna bracteata compost on ultisol soil medium and determine the dosage/dose of LCC Mucuna Bracteata compost which provides the best growth of oil palm seedlings (Elaeis guineensis Jacq). This research was carried out experimentally with a Completely Randomized Design (CRD), consisting of 5 treatments and 4 replications. The results of this study indicate that distributing doses of 400 g/8 kg of soil improved the physical and chemical properties of the soil and the vegetative growth of oil palm seeds.